The effects of Dendrobium species on the metabolic syndrome: A review - Zahra Oskouei; Mahboobeh Ghasemzadeh Rahbardar; Hossein Hosseinzadeh (Iranian Journal of Basic Medical Sciences, 2023)
Metabolic syndrome (MetS) is known as a global health challenge with different types of health conditions such as hypertension, hyperglycemia, the increasing prevalence of obesity, and hyperlipidemia. Despite much recent scientific progress, the use of traditional herbal medicines with fewer side effects is increasing worldwide. Dendrobium, the second-largest orchid genus, has been used as a natural source of drugs for the treatment of MetS. The beneficial effects of Dendrobium, including anti-hypertension, anti-hyperglycemia, anti-obesity, and anti-hyperlipidemic against MetS have been shown in the scientific evidence. The anti-oxidant and lipid-lowering effects of Dendrobium modulate hyperlipidemia via reducing lipid accumulation and maintaining lipid metabolism. Restoring pancreatic beta cells and regulating the insulin signaling pathway are involved in its antidiabetic properties. The hypotensive effects contribute to increasing nitric oxide (NO) generation and inhibiting extracellular signal-regulated kinase (ERK) signaling. More research projects, especially clinical trials, are needed to investigate the safety, efficacy, and pharmacokinetics of Dendrobium in patients. This review article provides, for the first time, comprehensive information about the efficacy of different species of Dendrobium. The described species can be a source of medicines for the treatment of MetS, which are reported in various evidence.